The better bond I have with my organization, the healthier I am! Correlates between organizational support and work-related injuries (Research, Society and Development, 2021)
The workers’ health has a significant influence on their quality of life, job satisfaction and performance. Many work situations can bring health risks, including work-related injuries. In this way, both the worker and the organization in general, must offer diagnostic actions, physical and mental health prevention and promotion for the entire work system. This article aims to verify the relationship between the organizational support perceived by workers and the assessment of work-related damage. 228 workers, over 18 years old, men and women, from the public and private sectors participated in the survey. They responded to the Perceived Organizational Support (POS), the Assessment Scale of Damage Related to Work (ASDRW) and to the socio-demographic data by electronic means using Google forms. It was observed that both scales showed reliable psychometric indicators and based on Pearson's correlation, organizational support was negatively and significantly correlated with the damage related to work and its respective dimensions (physical, psychological and social). It is understood that, in the conception of workers, the greater the support (support) It is understood that, in the workers' conception, the greater the support that the organization offers, the less chance that they will present more serious illnesses in the work environment. Based on the results, the need for multidisciplinary intervention programs with human resources developed by and within the organization with the aim of preventing, diagnosing and promoting the health of its workers is highlighted.